The Effectiveness of Assertive Training Techniques and Thought-Stopping Techniques to Increase Student Assertiveness Ability - Siti Zahra Bulantika; Permata Sari (Program Studi Bimbingan dan Konseling FKIP UMSU, 2019)
In carrying out activities, not all individuals/students can behave assertively and instead choose to act non-assertive (passive), such as harboring feelings, pretending, holding differences of opinion, or vice versa by being aggressive. Allowing yourself to be non-assertive can threaten the relationship because one party will feel used by the other party, not resolve the emotional problems they face, and can cause anxiety and stress. The purpose of this study is to examine the group counseling techniques assertive training and thought-stopping to improve student assertiveness abilities. Randomized Pretest-Postest Comparison Group Design for 24 students Bandar Lampung. The instrument used was an assertive scale by Fensterheim and Baer (1980). Data analysis techniques Paired sample t-test and one-way ANOVA. The results showed that group counseling for assertive training and thought-stopping techniques was effective in increasing student assertiveness. Findings prove the success of group counseling in assertive training and thought-stopping techniques for students in the city of Bandar Lampung.